ANALISIS CAMPUR KODE DALAM TUTURAN ANAK BILINGUAL PADA KONTEN DIGITAL: STUDI KASUS AKUN VANILLA LOVELY - Ridho Sastro Panjaitan; Adinda Andini; Melinda Maria Sitanggang; Melyanty Nababan; Shema Eklesiya Hutasoit; Yuni Tamba; Ayu Nadira Wulandari (Jurnal Padamu Negeri, 2026)
The development of social media platforms has produced a variety of digital content reflecting the language use of bilingual children, particularly the phenomenon of code-mixing between Indonesian and English in everyday interactions. This study analyzes the types and factors causing code-mixing in bilingual children's speech in videos from the Vanilla Lovely account using a descriptive qualitative sociolinguistic approach. Data in the form of children's dialogues were collected through observation and recording techniques, then analyzed to identify the types of code-mixing—the insertion of English words or phrases into Indonesian—and the factors that support it. The results indicate that code-mixing is triggered by the bilingual environment, exposure to digital media in a foreign language, and communication patterns within the family. This phenomenon functions as an informal communication strategy to facilitate the transmission of meaning. These findings highlight the role of digital content as a reflection of bilingual children's language practices in a multilingual society